Stability of the chlorinated derivatives of the DNA/RNA nucleobases, purine and pyrimidine toward radical formation via homolytic CCl bond dissociation. Issue 4 (18th November 2016) - Kaliyeva, Laura; Zhumagali, Shingis; Akhmetova, Nuriya; Karton, Amir; O'Reilly, Robert J.
Abstract: The chlorinated derivatives of nucleobases (and nucleosides), as well as those of purine, have well‐established anticancer activity, and in some cases, are also shown to be involved in the link between chronic inflammatory conditions and the development of cancer. In this investigation, the stability of all of the isomeric forms of the chlorinated nucleobases, purine and pyrimidine are investigated from the perspective of their homolytic CCl bond dissociation energies (BDEs). The products of these reactions, namely chlorine atom and the corresponding carbon‐centered radicals, may be of importance in terms of potentiating biological damage. Initially, the performance of a wide range of contemporary theoretical procedures were evaluated for their ability to afford accurate CCl BDEs, using a recently reported set of 28 highly accurate CCl BDEs obtained by means of W1w theory. Subsequent to this analysis, the G3X(MP2)‐RAD procedure (which achieves a mean absolute deviation of merely 1.3 kJ mol −1, with a maximum deviation of 5.0 kJ mol −1 ) was employed to obtain accurate gas‐phase homolytic CCl bond dissociation energies for a wide range of chlorinated isomers of the DNA/RNA nucleobases, purine and pyrimidine. Abstract : Chlorinated derivatives of nucleobases (and nucleosides) have well‐established anticancer activity, and in some cases, are also shown to be involved in the link between chronic inflammatory conditions and the development of cancer. Computational investigation contributes to shining a light on the stability of all of isomeric forms of the chlorinated nucleobases, as well as purine and pyrimidine. Their homolytic CCl bond dissociation is the key step in the formation of potentially damaging radical species.